Existence Results for Neutral Integro-Differential Equations with Unbounded Delay - Henriquez-Miranda, H (2011)
In this paper we discuss the existence of mild, strict and classical solutions for a class of abstract integro-differential equations in Banach spaces. Some applications to ordinary and partial integro-differential equations are considered. © 2011 Rocky Mountain Mathematics Consortium.